TOSLS: Development, Implementation, and Quality Analysis of an Instrument for Assessing Scientific Literacy - Pratiwi, Maulidatul Kurnia; Kuntjoro, Sunu; Sunarti, Titin; Budiyanto, Mohammad (Jurnal Penelitian dan Pembelajaran IPA, 2024)
The research aimed to develop an appropriate cognitive assessment for scientific literacy to measure science education students' abilities to identify learning strengths and weaknesses. This research used the R & D method. The normality test and a one-sample t-test was conducted. The specific topic covered in the research is fermented material. The study participants are science education students at a public university in Surabaya, Indonesia. The results indicated that the percentage of question difficulty levels, with 11.11% categorized as difficult and 44.44% categorized as easy. The analysis of test item discrimination reveals that 66.67% fall into the very good category, 11.11% into the good category, and 22.22% into the bad category. The one-sample t-test is conducted, yielding a significance value of 0.0314. Based on the obtained data, with 0.314 > 0.05, the null hypothesis (Ho) is accepted. This implies that the TOSLS instrument influences assessing students' level of scientific literacy ability. The findings of this study serve as a reference and best practice for tertiary institutions seeking to evaluate students' scientific literacy abilities.